As condições objetivas de vida da juventude vítima de homicídio na cidade de João Pessoa - Guedes, Italo de Oliveira (2020)
Youth is the main victim of homicide. Thus, this dissertation aims to analyze the objective life conditions of the youth victim of homicide in João Pessoa, with specific objectives of making a biosociodemographic characterization of that youth, characterizing the social context of the homicides, knowing the expressions of the social issue common to the youth that has been victim of homicide, identify criminalization processes that affect victims. The study was developed in two stages, based on documentary research with police investigations of homicides by the Civil Police. Using the SPSS software, a descriptive analysis of the biosociodemographic data of 136 surveys, defined from a sample calculation, was performed; in the second, nine cases were selected to perform thematic content analysis, using the MAXQDA software. It was observed that, of the victims, 58.1% were in the young-young age group, 99.2% were black people, 52.2% of the crimes occurred in only 10 neighborhoods in the city, 58.8% were murdered in the neighborhoods who lived, 60% were illiterate, 21.43% were considered “unemployed” and 91.2% of homicides used firearms. The content analysis revealed two major codes: blame by justice, composed of the categories Drug use, Absence of work activity, History of violence and Influence of friendships; and Social blame, with the categories Inefficiency of the State, Vulnerable territory and Early work. The findings show the existence of a specific pattern of mortality, which affects young, black men, with low education, living in poor neighborhoods and who develop precarious work activities. In addition, there was a criminalization process against youth that aims to justify the death of these young people and disconnect them from all contexts and structure of social classes that are inserted.